The Role of Education Colleges in Yemeni Universities to Develop Twenty-First Century Skills among Students - عبد الغني أحمد علي الحاوري; محمد عبد الله حسن حميد (University of Science and Technology, Yemen, 2021)
The study aimed to examine the role of colleges of education in Yemeni universities in developing the twenty-first century skills among students. The skills include critical thinking and problem-solving; creative thinking; effective communication and cooperation with others; flexibility; adaptation and change management; self and continuous learning; leadership and working with a team; taking responsibility and making decisions; using technology efficiently; understanding and interacting with diverse cultures; and work and self-management. The followed the descriptive and analytical method, using a questionnaire that was distributed to a random sample of (408) students selected from the fourth level of the Faculties of Education in four public universities: Sana'a, Hajjah, Amran, and Hodeidah.  The study results revealed a medium role that the colleges of education in Yemeni universities play in developing the twenty-first century skills among their students. The skill of effective communication and cooperation with others received the highest attention, while the skills of work, self-management and the skills of using technology efficiently received the lowest level of attention.  The study concluded with a number of conclusions, including absence of a vision for the challenges and requirements of the twenty-first century and lack of support provided to colleges to purchase facilities and equipment. The study recommended that the colleges of education should pay more attention to developing the twenty-first century skills, especially work and self-management skills and the efficient use of technology. Keywords: role, education college, skills, twenty-first century, Yemeni universities.